Numerical Deformation Analysis of Bridge Concrete Girders - Gintaris Kaklauskas; Rokas Girdžius; Darius Bačinskas; Aleksandr Sokolov (The Baltic Journal of Road and Bridge Engineering, 2008)
Present research was aiming at deriving tension stiffening relationship based on EC2 provisions for deformation analysis of bending RC structures. According to the algorithm proposed by the first author, a tension stiffening relationships were derived from moment-curvature diagrams of reinforced concrete beams calculated according to EC2 technique. The obtained tension stiffening relationship was applied in the parametric study, using non-linear finite element software ATENA and layered model. Theoretical results were compared with experimental data of beams reported in the literature. The defined tension stiffening relationship was also applied for calculation of moment-curvature response of reinforced concrete bridge girder. The analyses have shown that the deformations calculated using the derived tension stiffening relationship and the EC2 technique were in good agreement.